2014
DOI: 10.1177/0363546513518415
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Repair for Cartilage Defects in a Rabbit Model

Abstract: Microfracture combined with a DCCBM scaffold is a promising method that can be performed and adopted into clinical treatment for articular cartilage injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…A trapezoidal load function was applied to each indent site with loading (10 s), holding (2 s), and unloading (10 s). The microscopic geomorphology of the indentation zones was captured using a micro-scanning apparatus39. The mechanical properties of the chondrocytes were measured using a Bioscope Resolve AFM (Bruker AXS Corporation, Santa Barbara, CA), following previously established techniques40.…”
Section: Methodsmentioning
confidence: 99%
“…A trapezoidal load function was applied to each indent site with loading (10 s), holding (2 s), and unloading (10 s). The microscopic geomorphology of the indentation zones was captured using a micro-scanning apparatus39. The mechanical properties of the chondrocytes were measured using a Bioscope Resolve AFM (Bruker AXS Corporation, Santa Barbara, CA), following previously established techniques40.…”
Section: Methodsmentioning
confidence: 99%
“…However, five years after surgery higher incidences of clinical failures are observed ( Hoemann et al, 2010 ; Van der Linden et al, 2013 ). The newly formed tissue generally consists of fibrocartilage repair tissue rather than hyaline cartilage, has limited filling of the defect, integrates poorly with the surrounding tissue and has inferior mechanical properties compared to hyaline cartilage ( Dai et al, 2014 ). Therefore, the need for regeneration of more durable cartilage tissue persists.…”
Section: Introductionmentioning
confidence: 99%
“…Known as DeNovo ET, the technology would be available as an off-the-shelf option that uses minced allograft donor cartilage to fill chondral defects and has been demonstrated to generate cartilage similar to physiologic hyaline baseline. 40 , 61 Other novel techniques are attempting to evolve a single-step cartilage repair procedure, 6 , 7 , 18 one such example being the Cartilage Autograft Implantation System (CAIS). In a preclinical animal study, Frisbie et al 33 demonstrated CAIS and ACI as superior to an empty defect (negative control) in equine articular defects, with CAIS being superior to ACI.…”
Section: Clinical Application Of In Vitro–engineered Implantsmentioning
confidence: 99%
“… 14 In recent advances, multiple studies have documented several different techniques, some combining microfracture with biocompatible matrices and others using novel cell mixtures alone, both of which have shown the ability to proliferate a hyaline-like repair in isolated defects. 6 , 18 Certain techniques look to use stem cells to augment the existing ACI protocol, achieving proliferation and development in a single-step procedure. 7 These types of innovation are significant, as a single-step repair procedure would serve as a point-of-care surgical procedure for the primary treatment of isolated, full-thickness chondral lesions in the knee and decrease return trips to the operating room.…”
Section: Clinical Application Of In Vitro–engineered Implantsmentioning
confidence: 99%